Characteristics and Management of Peatland for Agricultural Development - N.P. Sri Ratmini (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Ratmini, 2012. Characteristics and Management of Peatland for Agricultural Development. JLSO 1(2):197-206 The potential of peatland as agricultural land has area of about 6 M ha. The utilization of peatland in agriculture need detail and thorough planning, adequate technology application, and proper land management because its marginal and fragile ecosystem. Peatland is vulnerable to land degradation, namely physical degradation (subsiden and irreversible drying) and chemical degradation (nutrients deficiency and nutrients toxicity). The peatland development has obstacles such as highly content of organic acids. The effect of organic acid toxicity can be reduced by water (irrigation technology) management and adding ameliorant which rich of polivalent cation such as Fe, Al, Cu, and Zn. Soil amendment and fertilization in peatland farming can be done to reduce nutrients deficiency.